The Earnings Outcomes of Overeducation in the Early Years of an Australian Career. - Kaye, Lauren (My University, 2012)
The occurrence of overeducation can have many varied outcomes in the labour market. This paper analyses the expected financial outcome of being overeducated for individuals aged between 22 and 33. In order to estimate the outcome this paper utilises the panel nature of the HILDA data set to estimate the fixed effects outcome. This paper classifies overeducation in a way that has not been done previously in order to see if the same outcomes are reached.
Keywords: Education and Training -- Educational level; Income & Finance -- Income inequality; Income, wealth and finances; Learning, education and training; Education and Training; Income & Finance; Income inequality; Educational level; Income, wealth and finances; Learning, education and training